Implementasi Inovasi Pendidikan Akhlak Pendekatan Saintifik Berbasis Manajemen Qolbu - Anas Amin Alamsyah (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
The impact of evil is felt in almost every aspect of community life. This happens because the spectrum of evil is so widened that it encompasses various aspects of social life. That is one of the phenomenon of moral crisis that is now befall our nation. In addition, there are still many other moral matters, such as drunkenness, drug abuse, bribery and so forth. Based on the background of the problem and the formulation of the above problems, the author hopes that this paper can be a contribution of thought for education to achieve a better change The purpose of this paper is: To examine how to implement the Innovation of Education Innovation Akhlak Scientific Approach-Based Qolbu Management. The type of research in this research is qualitative that is focusing on library research (library research), where the author uses descriptive research method with more emphasis on the power of data analysis on the sources in the can from books and other scientific papers by relying theories that exist to be interpreted widely and deeply. The results of this study can be mentioned that the way of implementing the Innovation of Educational Innovation Scientific Approach Based on Qolbu Management is: 1) Tazkiyah an Nafs (purification of the soul), 2) Tasyfiyah al Qolb (cleansing of the heart), 3) Tajalliyah ar ruh (enlightenment spirit). Furthermore, in the opinion of Aa Gym which is also similar to Ibn Miskawayih's opinion that there are several steps that must be taken to cleanse the heart, among others: 1) The existence of strong adherence, 2) Have knowledge about understanding or self-knowledge, 3) Evaluate yourself , 4) Learning from others. The conclusion that got is that Implementation of Innovation of Education Akhlak Scientific Approach-Based Management Qolbu is a new idea or method offered by the author for use in implementing moral education. It is expected that this new idea or method, will be able to improve the quality of moral education that is felt increasingly declining today.